Quasi-static axial crushing of single wall corrugated paperboard. (15th October 2019) - Bai, Jing; Wang, Jun; Pan, Liao; Lu, Lixin; Lu, Guoxing
Abstract: The axial crushing of the single wall corrugated paperboard is explored experimentally and analytically. Quasi-static compression experiment is conducted of the single wall corrugated paperboard, and a typical folding element is suggested based on the selection principle of the unit, including two corner elements and two panels. Then, a theoretical model is derived to predict the plateau stress of the corrugated paperboard. It is show that the prediction of plateau stress from the model compares well with the experimental results. Moreover, it is found that the fluted board contributes more to the total energy dissipation than the liner. The results may help to reveal the deformation mechanism and crush resistance of the single wall corrugated paperboard.